Rethinking the risks of poverty: a framework for analyzing prevalences and penalties - David Brady; Ryan M. Finnigan; Sabine Hübgen (Luxembourg Income Study (LIS), 2017)
Considerable attention focuses on the risks of poverty, defined as individual-level labor market and family characteristics more common among the poor than the non-poor. This article first develops a framework for analyzing the risks of poverty in terms of prevalences (share of the population with a risk) and penalties (increased probability of poverty associated with a risk). Comparing the four major risks (low education, single motherhood, young headship, and unemployment) across 29 rich democracies, we show there is greater variation in penalties than prevalences. Second, we apply this framework to the U.S. We show that prevalences cannot explain high U.S. poverty as the U.S. has below average prevalences. Rather, the U.S. has high poverty partly because it has the highest penalties. U.S. poverty would decline more with crossnational median penalties than cross-national median prevalences, and U.S. poverty in 2013 would actually be worse with prevalences from 1970 or 1980. Third, we analyze cross-national variation in prevalences and penalties. We find very little evidence that higher penalties discourage prevalences, or that lower penalties encourage prevalences. We also show welfare generosity significantly moderates the penalties for unemployment and low education. We conclude with three broader implications. First, a focus on risks is unlikely to provide a convincing explanation or effective strategy for poverty. Second, despite being the subject of the most research, single motherhood may be the least important of the risks. Third, for general explanations of poverty, studies based solely on the U.S. are constrained by potentially large sample selection biases.
Keywords: 330